ANALISIS PENGARUH NET PROFIT MARGIN (NPM), RETURN ON EQUITY (ROE), DAN DEBT TO EQUITY RATIO (DER) TERHADAP PERTUMBUHAN LABA PT HARTADINATA ABADI TBK PERIODE 2017-2023 (PER KUARTAL) - Yamin, Mohammad; Nur Aini, Dewi (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This study aims to determine the effect of Net Profit Margin (NPM), Return On Equity (ROE), and Debt ToEquity Ratio (DER) on profit growth. The data used in this study are secondary data obtained throughthe financial statements of PT Hartadinata Abadi Tbk for the period 2017-2023 per quarter. The methodused in this research is multiple linear regression, involving the classical assumption test, followed bypartial significance using the T test hypothesis test using the SPSS version 25 program. The results of thisstudy indicate that of the three independent variables analyzed, Net Profit Margin (NPM), and Return OnEquity (ROE) have no significant effect on Earnings Growth. While the Debt To Equity Ratio (DER)variable on Profit Growth. The projection ability of the three independent variables on Earnings Growthis 19.6% as indicated by the amount of adjust R2, the remaining 80.4% is explained by other variablesoutside the research model.